PillCam® SB3 capsule: does the increased frame rate eliminate the risk of missing lesions? - Monteiro, Sara (2016)
Since its emergence in 2000, small bowel capsule endoscopy (SBCE) has assumed a pivotal role as an investigation method for small bowel diseases. The PillCam (R) SB2-ex offers 12 h of battery time, 4 more than the previous version (SB2). Rahman et al recently found that the PillCam (R) SB2-ex has a significantly increased completion rate, although without higher diagnostic yield, compared with the SB2. We would like to discuss these somewhat surprising results and the new potentialities of the PillCam (R) SB3 regarding the diagnostic yield of small bowel studies. PillCam (R) SB3 offers improved image resolution and faster adaptable frame rate over previous versions of SBCE. We recently compared the major duodenal papilla detection rate obtained with PillCam (R) SB3 and SB2 as a surrogate indicator of diagnostic yield in the proximal small bowel. The PillCam (R) SB3 had a significantly higher major duodenal papilla detection rate than the PillCam (R) SB2 (42.7% vs 24%, P = 0.015). Thus, the most recent version of the PillCam (R) capsule, SB3, may increase diagnostic yield, particularly in the proximal segments of the small bowel.